2018
DOI: 10.1177/1354816618812297
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ perceived corporate social responsibility evaluation and support: The moderating role of consumer information

Abstract: This study analyzes how consumers' evaluations of various dimensions of corporate social responsibility (CSR) affect their support of it and how consumers' searches for CSR information influence such evaluations. The empirical analysis relies on data on CSR from a wide representative sample of 3543 Spanish hotel consumers. We use hierarchical multiple regressions to test the relationships and use factorial analysis to test the validity of the different CSR dimensions. The proposed positive effects of legal, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 140 publications
(227 reference statements)
0
13
0
Order By: Relevance
“…CSR originates more at the meso-level, aiming to contribute to sustainability. Thus, organizations and its stakeholders are key players in the endeavor to achieve sustainability (Boronat-Navarro & Pérez-Aranda, 2019). Two of the most popular definitions of CSR come from Carroll (1979Carroll ( , 1998 who established CSR's four main dimensions (economic, legal, ethical, and philanthropic), and from the World Business Council for Sustainable Development (WBCSD; 1999), which states, "Corporate social responsibility is the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as the local community and society at large" (p. 3).…”
Section: Csr Backgroundmentioning
confidence: 99%
“…CSR originates more at the meso-level, aiming to contribute to sustainability. Thus, organizations and its stakeholders are key players in the endeavor to achieve sustainability (Boronat-Navarro & Pérez-Aranda, 2019). Two of the most popular definitions of CSR come from Carroll (1979Carroll ( , 1998 who established CSR's four main dimensions (economic, legal, ethical, and philanthropic), and from the World Business Council for Sustainable Development (WBCSD; 1999), which states, "Corporate social responsibility is the continuing commitment by business to behave ethically and contribute to economic development while improving the quality of life of the workforce and their families as well as the local community and society at large" (p. 3).…”
Section: Csr Backgroundmentioning
confidence: 99%
“…This model addresses the needs of business, labour and local development, providing added value that is useful to promote and popularize the true relevance of CSR and sustainability among clients and employees. These principles have a positive impact on the hotels that commit to them [12][13][14]16,17,[19][20][21]26,43,71,72]. The model also has implications for attracting and retaining talent because potential employees in the sector can choose those companies that have exemplary labour practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to analyse the relationship between CSR and company performance, and also that the credibility of the results needs to be improved [12], an increasing number of studies have shown that CSR is a useful construct by which to identify new segments of clients committed to social development in tourism. CSR represents an opportunity for hotels to differentiate themselves from other competitors thanks to its impact on improving the image of the hotel, client loyalty, and trust [13][14][15][16]. Recently, other authors have reached similar conclusions, suggesting that CSR practices improve the competitive position of companies [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…Corporate behavior, stakeholder participation in CSR management based on issue identification, and an integrated communication strategy are three fundamental premises to solidify a positive reputation, based ethics and responsible advocacy [6][7][8]. The inherent complexity and challenges of relationship management highlight the need to implement and improve corporate communication channels to achieve strategic goals.…”
Section: Introductionmentioning
confidence: 99%